2020
DOI: 10.12659/msm.919888
|View full text |Cite
|
Sign up to set email alerts
|

In-depth analysis of risk factors for recurrence of lumbar 5-sacral 1 disc herniation after Percutaneous endoscopic transforaminal discectomy

Abstract: Background:This retrospective study aimed to investigate the risk factors associated with the recurrence of L5-S1 disc herniation after percutaneous endoscopic transforaminal discectomy (PETD). Material/Methods:There were 484 patients L5-S1 disc herniation who underwent PETD who were divided into the recurrence group (n=46) and the non-recurrence group (n=438). Transforaminal endoscopic approaches included modifications of the Yeung endoscopy spine system (YESS) (the intraforaminal intradiscal approach) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 47 publications
1
31
1
Order By: Relevance
“…The present study found that the incidence of rLDH was higher in discs with moderate degeneration (grade III) than discs with mild degeneration (grade II), which is consistent with previous correlational research. 20 Severely degenerated discs (grades IV and V) also experienced infrequent rLDH in the present study. Relevant cadaveric and clinical studies demonstrated that the range of segmental motion in degenerated and collapsed discs decreased in proportion to the degree of degeneration.…”
Section: Discussionsupporting
confidence: 59%
“…The present study found that the incidence of rLDH was higher in discs with moderate degeneration (grade III) than discs with mild degeneration (grade II), which is consistent with previous correlational research. 20 Severely degenerated discs (grades IV and V) also experienced infrequent rLDH in the present study. Relevant cadaveric and clinical studies demonstrated that the range of segmental motion in degenerated and collapsed discs decreased in proportion to the degree of degeneration.…”
Section: Discussionsupporting
confidence: 59%
“…A possible explanation is that returning to work and activity prematurely may increase lumbar loading and stimulate inflammatory responses in the surgical area, contributing to the development of postoperative rebound pain. Maybe because of busy work, the average return‐to‐work time in the rebound pain group was 29.0 ± 7.9 days, which was much shorter than 6–16 weeks reported in other research 30 , 31 . It also reminded us that we should be alert to related complications, while achieving enhanced recovery after surgery.…”
Section: Discussionmentioning
confidence: 53%
“…A previous study reported that the growth of scar tissue after surgery can surround and protect the nucleus pulposus tissue. 29 Undoubtedly, this procedure helps stabilize the intervertebral space. Care should be taken to maintain the lumbar spine after surgery, such as not bending frequently, not lifting heavy objects and not maintaining the same position for long periods of time.…”
Section: Discussionmentioning
confidence: 99%